Entropy is Key to the Formation of Pentacyclic Terpenoids by Enzyme‐Catalyzed Polycyclization1. (7th April 2014) - Syrén, Per‐Olof; Hammer, Stephan C.; Claasen, Birgit; Hauer, Bernhard
Abstract Polycyclizations constitute a cornerstone of chemistry and biology. Multicyclic scaffolds are generated by terpene cyclase enzymes in nature through a carbocationic polycyclization cascade of a prefolded polyisoprene backbone, for which electrostatic stabilization of transient carbocationic species is believed to drive catalysis. Computational studies and site‐directed mutagenesis were used to assess the contribution of entropy to the polycyclization cascade catalyzed by the triterpene cyclase from A. acidocaldarius. Our results show that entropy contributes significantly to the rate enhancement through the release of water molecules through specific channels. A single rational point mutation that results in the disruption of one of these water channels decreased the entropic contribution to catalysis by 60 kcal mol−1. This work demonstrates that entropy is the key to enzyme‐catalyzed polycyclizations, which are highly relevant in biology since 90 % of all natural products contain a cyclic subunit.